The quasi-static compressive mechanical properties of barnacle bioinspired structures. (15th January 2023) - Xiang, Xinmei; Xiao, Chenkun; Ha, Ngoc San; Lu, Guoxing; Zhang, Shaolin; Liu, Yijie
Highlights: 3D printed bioinspired tapered tubes based on observations of barnacles are designed. The mechanical properties of the tubes under quasi-static compression loads are studied experimentally, numerically and theoretically. The effects of the number of corrugations and the corrugation amplitudes on the structural deformation and energy absorption performance are obtained. The crashworthiness of the corrugated tapered tubes under oblique loads is investigated. Abstract: Thin-walled structures are widely used as energy absorption devices in vehicles. This paper designs bioinspired thin-walled structures based on observations of barnacles and studies the mechanical properties of these structures under quasi-static conditions. The effects of the number of corrugations and the corrugation amplitudes on the structural deformation and energy absorption performance of 3D printed bioinspired tapered tubes are studied experimentally, numerically, and theoretically. The results show that the corrugation amplitude and the number of corrugations have a significant influence on the energy absorption parameters, and the specific energy absorption (SEA) can be significantly improved when the number and amplitude of the corrugations are properly controlled. The highest SEA of the corrugated tapered tube can be improved by 15.75% compared with the traditional tapered tube. Furthermore, the crashworthiness of the corrugated tapered tubes under oblique loads is also investigated. The result shows that the SEA of the corrugated tapered tube is 41.56% higher than that of the cylindrical tube when the oblique loading angle is 20°. Finally, the energy absorption performance of the multicell structures is studied, and they perform much better than conventional structures. Especially, the SEA of the multicell tapered tube with 16 cells is approximately 1.97 times that of conventional tube.